A new voluntary blood collection method for the Andean bear (Tremarctos ornatus) and Asiatic black bear (Ursus thibetanus). Issue 5 (21st July 2015) - Otaki, Yusuke; Kido, Nobuhide; Omiya, Tomoko; Ono, Kaori; Ueda, Miya; Azumano, Akinori; Tanaka, Sohei
<x xml:space="preserve">Abstract</x> Various training methods have been developed for animal husbandry and health care in zoos and one of these trainings is blood collection. One training method, recently widely used for blood collection in Ursidae, requires setting up a sleeve outside the cage and gives access to limited blood collection sites. A new voluntary blood collection method without a sleeve was applied to the Andean bear (Tremarctos ornatus) and Asiatic black bear (Ursus thibetanus) with access to various veins at the same time. The present study evaluated the effectiveness of this new method and suggests improvements. Two Andean and two Asiatic black bears in Yokohama and Nogeyama Zoological Gardens, respectively, were trained to hold a bamboo pipe outside their cages. We could, thereby, simultaneously access superficial dorsal veins, the dorsal venous network of the hand, the cephalic vein from the carpal joint, and an area approximately 10 cm proximal to the carpal joint. This allowed us to evaluate which vein was most suitable for blood collection. We found that the cephalic vein, approximately 10 cm proximal to the carpal joint, was the most suitable for blood collection. This new method requires little or no modification of zoo facilities and provides a useful alternative method for blood collection. It could be adapted for use in other clinical examinations such as ultrasound examination. Zoo Biol. 34:497–500, 2015. © 2015 Wiley Periodicals, Inc.